A Prospective Study of Optic Nerve Ultrasound for the Detection of Elevated Intracranial Pressure in Severe Traumatic Brain Injury. Issue 12 (December 2020) - Agrawal, Deepak; Raghavendran, Krishnan; Zhao, Lili; Rajajee, Venkatakrishna
Abstract : Objectives: Intracranial pressure monitoring plays a critical role in the management of severe traumatic brain injury. Our objective was to evaluate the accuracy of optic nerve sheath diameter as a noninvasive screening test for the detection of elevated intracranial pressure and prediction of intracranial pressure treatment intensity. Design: Prospective, blinded study of diagnostic accuracy. Setting: Neurotrauma ICU. Subjects: Consecutive patients with severe traumatic brain injury. Interventions: Optic nerve ultrasound was performed daily and optic nerve ultrasound measured at the point-of-care as well as remotely by an expert blinded to all patient details. Optic disc elevation was also measured. The index test was the highest remote-expert optic nerve ultrasound for the admission. The reference standard was the concurrent invasive intracranial pressure, with test-positivity set at intracranial pressure greater than 22 mm Hg. A priori the minimally acceptable sensitivity threshold was 90% with corresponding specificity 60%. We also evaluated the ability of optic nerve ultrasound to predict a therapeutic intensity level greater than 10. Measurements and Main Results: One hundred twenty patients were enrolled. The intraclass correlation coefficient between point of care and expert optic nerve sheath diameter after enrollment of 50 subjects was poor at 0.16 (–0.08 to 0.41) but improved to 0.87 (0.81–0.92) for the remaining subjects after remedial training. The area under the curve of the receiver operating characteristic curve of the highest expert-measured optic nerve sheath diameter to detect intracranial pressure greater than 22 mm Hg was 0.81 (0.73–0.87); area under the curve for prediction of therapeutic intensity level greater than 10 was 0.51 (0.42–0.60). Optic nerve sheath diameter greater than 0.72 demonstrated sensitivity 82% (48–98%) and specificity 79% (70–86%) for intracranial pressure greater than 22 mm Hg. The area under the curve of highest measured optic disc elevation to detect intracranial pressure greater than 22 mm Hg was 0.84 (0.76–0.90). Optic disc elevation greater than 0.04 cm attained sensitivity 90% (56–100%) and specificity 71% (61–79%). Conclusions: While optic nerve sheath diameter demonstrated a modest, statistically significant correlation with intracranial pressure, a predetermined level of diagnostic accuracy to justify routine clinical use as a screening test was not achieved. Measurement of optic disc elevation appears promising for the detection of elevated intracranial pressure, however, verification from larger studies is necessary.